Hoarding and depression: The mediating role of perceived burdensomeness. (December 2016) - Raines, Amanda M.; Short, Nicole A.; Fuller, Kelly L.; Allan, Nicholas P.; Oglesby, Mary E.; Schmidt, Norman B.
Abstract: Despite clear indications that hoarding behaviors contribute to social isolation and strained family relationships, no research to date has examined the associations between hoarding and several important interpersonal constructs (i.e., perceived burdensomeness and thwarted belongingness). Moreover, no research has examined how these various interpersonal needs may account for the associations between symptoms of hoarding and depression. Community participants (N = 125) with elevated hoarding symptoms were assessed on the interpersonal constructs of interest. Hoarding severity was significantly associated with perceived burdensomeness even after controlling for overall levels of negative affect. Moreover, perceived burdensomeness significantly mediated the relationship between hoarding severity and depressive symptoms. To our knowledge this is the first study to examine potential mechanisms that may account for the robust associations between hoarding and depression. Future investigations should attempt to replicate these findings using clinical samples.